61.5.16 problem 16

Internal problem ID [12140]
Book : Handbook of exact solutions for ordinary differential equations. By Polyanin and Zaitsev. Second edition
Section : Chapter 1, section 1.2. Riccati Equation. subsection 1.2.4-1. Equations with hyperbolic sine and cosine
Problem number : 16
Date solved : Tuesday, January 28, 2025 at 07:12:25 PM
CAS classification : [_Riccati]

\begin{align*} \left (a \cosh \left (\lambda x \right )+b \right ) y^{\prime }&=y^{2}+c \cosh \left (\mu x \right ) y-d^{2}+c d \cosh \left (\mu x \right ) \end{align*}

Solution by Maple

Time used: 0.007 (sec). Leaf size: 268

dsolve((a*cosh(lambda*x)+b)*diff(y(x),x)=y(x)^2+c*cosh(mu*x)*y(x)-d^2+c*d*cosh(mu*x),y(x), singsol=all)
 
\[ y = \frac {-d \left (\int \frac {{\mathrm e}^{\frac {c \left (\int \frac {\cosh \left (\mu x \right )}{a \cosh \left (\lambda x \right )+b}d x \right ) \sqrt {a^{2}-b^{2}}\, \lambda -4 d \arctan \left (\frac {\left (a -b \right ) \tanh \left (\frac {\lambda x}{2}\right )}{\sqrt {a^{2}-b^{2}}}\right )}{\sqrt {a^{2}-b^{2}}\, \lambda }}}{a \cosh \left (\lambda x \right )+b}d x \right )+d c_{1} -{\mathrm e}^{\frac {c \left (\int \frac {\cosh \left (\mu x \right )}{a \cosh \left (\lambda x \right )+b}d x \right ) \sqrt {a^{2}-b^{2}}\, \lambda -4 d \arctan \left (\frac {\left (a -b \right ) \tanh \left (\frac {\lambda x}{2}\right )}{\sqrt {a^{2}-b^{2}}}\right )}{\sqrt {a^{2}-b^{2}}\, \lambda }}}{\int \frac {{\mathrm e}^{\frac {c \left (\int \frac {\cosh \left (\mu x \right )}{a \cosh \left (\lambda x \right )+b}d x \right ) \sqrt {a^{2}-b^{2}}\, \lambda -4 d \arctan \left (\frac {\left (a -b \right ) \tanh \left (\frac {\lambda x}{2}\right )}{\sqrt {a^{2}-b^{2}}}\right )}{\sqrt {a^{2}-b^{2}}\, \lambda }}}{a \cosh \left (\lambda x \right )+b}d x -c_{1}} \]

Solution by Mathematica

Time used: 6.814 (sec). Leaf size: 289

DSolve[(a*Cosh[\[Lambda]*x]+b)*D[y[x],x]==y[x]^2+c*Cosh[\[Mu]*x]*y[x]-d^2+c*d*Cosh[\[Mu]*x],y[x],x,IncludeSingularSolutions -> True]
 
\[ \text {Solve}\left [\int _1^x-\frac {\exp \left (-\int _1^{K[2]}\frac {2 d-c \cosh (\mu K[1])}{b+a \cosh (\lambda K[1])}dK[1]\right ) (-d+c \cosh (\mu K[2])+y(x))}{c \mu (b+a \cosh (\lambda K[2])) (d+y(x))}dK[2]+\int _1^{y(x)}\left (\frac {\exp \left (-\int _1^x\frac {2 d-c \cosh (\mu K[1])}{b+a \cosh (\lambda K[1])}dK[1]\right )}{c \mu (d+K[3])^2}-\int _1^x\left (\frac {\exp \left (-\int _1^{K[2]}\frac {2 d-c \cosh (\mu K[1])}{b+a \cosh (\lambda K[1])}dK[1]\right ) (-d+c \cosh (\mu K[2])+K[3])}{c \mu (b+a \cosh (\lambda K[2])) (d+K[3])^2}-\frac {\exp \left (-\int _1^{K[2]}\frac {2 d-c \cosh (\mu K[1])}{b+a \cosh (\lambda K[1])}dK[1]\right )}{c \mu (b+a \cosh (\lambda K[2])) (d+K[3])}\right )dK[2]\right )dK[3]=c_1,y(x)\right ] \]